The British textile trade in South America in the nineteenth century - Llorca-Jaña, Manuel 1975- (Cambridge Latin American studies, 2012)
This is the first work on British textile exports to South America during the nineteenth century. During this period, textiles ranked among the most important manufactures traded in the world market and Britain was the foremost producer. Thanks to new data, this book demonstrates that British exports to South America were transacted at very high rates during the first decades after independence. This development was due to improvements in the packing of textiles; decreasing costs of production and introduction of free trade in Britain; falling ocean freight rates, marine insurance and import duties in South America; dramatic improvements in communications; and the introduction of better port facilities. Manuel Llorca-Jaña explores the marketing chain of textile exports to South America and sheds light on South Americans' consumer behaviour. This book contains the most comprehensive database on Anglo-South American trade during the nineteenth century and fills an important gap in the historiography